Washington and Copenhagen.
The US government has been having a very hard time developing, out of a nation disunited on climate, a united position for the Copenhagen negotiations.
Keywords: Climatic changes -- Economic aspects; Climatic changes -- Government policy; Climatic changes -- International cooperation